Effect of residual carbon on crystallization and solidification behavior of coal gasification coarse slag - Ze Meng; Rongsheng Xu; Qian Feng; Xiongchao Lin; Mei Li (International Journal of Coal Science & Technology)
Abstract This work investigates the influence of carbon residue on the crystallization and solidification behavior of slag at different temperatures and cooling methods as it has a significant impact on the flow and discharge of slag, as well as the proper functioning of gasification equipment. The experimental approach involves the utilization of various techniques, namely ash fusion temperature (AFT) tests, X-ray fluorescence spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), differential thermal analysis (DSC), and K-value semiquantitative analysis. The results obtained from ash fusion temperature (AFT) tests indicate that the coarse slag exhibits a relatively higher flow temperature compared to the decarburized coarse slag. XRD analysis reveals the presence of diffraction peaks corresponding to Fe and Fe3Si when residue carbon is present in the slag. In contrast, no such peaks are observed in the decarburized coarse slag subjected to the same temperature and cooling mode. This implying that the carbothermal reaction affects the slag's crystallization behavior, consequently influencing the flow temperature in the presence of residual carbon. SEM analysis illustrates that the spheroidization phenomenon is obvious when there is residual carbon in the coarse slag, but there is no spheroidization phenomenon in the decarburized coarse slag. This shows that the surface tension of slag is affected by the presence of residual carbon. Furthermore, DSC results confirm the crystallization transformation and mineral decomposition of the slag at high temperatures. For both carbon-containing slag and decarburized coarse slag, the content of crystals obtained under quenching condition is obviously lower than that under natural cooling condition.